(untitled) (Bangladesh Journal of Agricultural Research, 2020)
An experiment was conducted in the research field of Pulses Research Sub-Station, BARI, Gazipur during two consecutive years of 2015-16 and 2016-17 to determine the suitable dose of potassium for achieving higher yield attributes, nodulation, nutrient concentration and yield maximization of lentil. There were 5 treatments viz. T1 = Control, T2 = 30 kg K ha-1, T3= 40 kg K ha-1, T4= 50 kg K ha-1 and T5= 60 kg K ha-1 along with the blanket dose of fertilizers of N, P, S, Zn and B @ 15, 20, 10, 2 and 1.5 kg ha-1, respectively for all treatments. The experiment was laid out in randomized complete block design (RCBD) with three replications. Results revealed that the highest seed yield (1092 kg ha-1) of lentil (mean of two years) was found in T4 followed by T5 treatment and the lowest (736 kg ha-1) was noted in K control (T1) treatment. The highest % yield increase over control (48.3%) was recorded from T4 treatment. The maximum nodulation was found in T5 followed by T4 treatment. The highest protein (26.9%), N, P, K, S, Zn and B concentrations of lentil seed were recorded in T4 treatment. Therefore, the results suggest that the appliction of 50 kg K ha-1 along with N15P20S10Zn2B1.5 kg ha-1 are optimum for achieving higher yield potential of lentil in terrace soils of Bangladesh. Bangladesh J. Agril. Res. 44(4): 599-607, December 2019